Platelet-rich plasma injection for tennis elbow: did it ever work?. Issue 1 (11th January 2022) - Karjalainen, Teemu; Richards, Bethan; Buchbinder, Rachelle
Abstract : Platelet-rich plasma (PRP) is a commonly used treatment for tendinopathies such as tennis elbow despite the questionable evidence of its efficacy. A recent Cochrane review suggests that it likely does not provide clinically meaningful benefits in people with tennis elbow. In this viewpoint, we discuss how lack of regulation allowed aggressive marketing and clinical use without normal phases of drug development and approval process or rigorous evidence of benefits. Since several phases of development were bypassed, we still do not know the optimal preparation method and dosing of PRP for tendinopathies. Furthermore, several clinical trials compared PRP with other interventions although it was unclear if PRP was better than placebo and these comparisons created distraction rather than improved understanding of its effects.